Wattpad’s Role in Motivating Secondary School Students to Write a Narrative Text: A Case Study - Dwi Agustina; Rahmad Hidayat (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
This study aims to investigate Wattpad's role in motivating secondary school students to write narrative texts. As an online application, Wattpad offers several benefits for students, particularly those with low motivation in writing due to difficulties learning vocabulary and a lack of ideas or inspiration when composing a narrative text. Therefore, exploring the efforts of students who utilize Wattpad to develop their writing skills is interesting, specifically by using narrative texts as the application's content. This research employed a qualitative case study approach, in which the researcher conducted interviews with three 11th-grade students from SMA Negeri 1 Wringinanom during the academic year 2022/2023. The data obtained from the interviews were then analyzed using the Miles and Huberman model. The study findings revealed that Wattpad significantly motivates secondary school students to write narrative texts. The platform aids students in nurturing their imagination and discovering new vocabulary through the narrative stories on the Wattpad application. Furthermore, the study suggests that students with writing talent can further develop their skills on this platform, allowing their work to be recognized and read by a wider audience.